Perancangan Sistem Pengendalian Tegangan Tinggi X - Ray Medis Menggunakan Pulse Width Modulation (PWM) Dengan Implementasi Berbasis Java - Andi Muhammad Iqbal; Riswal Nafi Siregar (CV. Multi Kreasi Media, 2025)
This study aims to design and implement a high-voltage control system for a prototype-scale medical X-Ray device using the Pulse Width Modulation (PWM) method, controlled via an Arduino microcontroller and a Java-based user interface. The system is developed to allow dynamic adjustment of PWM duty cycle, with output voltage responding proportionally to changes in PWM values. Experimental results show a nearly linear relationship between PWM and voltage, indicating that PWM is a stable and effective method for voltage regulation. Additionally, the developed Java interface enables users to set PWM values, exposure duration, and monitor system status in real-time without direct hardware interaction, enhancing operational safety and usability. The system is equipped with an automatic protection mechanism based on voltage feedback from the ADC; the microcontroller will automatically stop the exposure process if the voltage exceeds a predefined threshold. This feature has proven effective in preventing damage due to overvoltage. Overall, the system meets the primary research objective—creating a measurable, safe, and externally integrated high-voltage control mechanism. This research contributes to the advancement of more efficient and adaptable X-Ray control technologies suitable for medical and laboratory applications.